EXTREME LASER RADIATION: PHYSICS AND FUNDAMENTAL APPLICATIONS : Quantum-mechanical calculations of residual current density excited during gas ionisation by an intense two-colour laser pulse. (1st June 2016) - Vvedenskii, N V; Romanov, A A; Silaev, A A
Abstract: By solving analytically and numerically the three-dimensional time-dependent Schrödinger equation, we have studied the excitation of a residual current density during gas ionisation by a two-colour laser pulse containing a field at the fundamental frequency and an additional field at the doubled frequency. We have found the dependences of the residual current density on the phase shift between the components of the field and on the intensity of the fundamental harmonic. It is shown that the strong-field approximation taking into account the interaction of freed electrons with the parent ion yields a good quantitative agreement with the results of direct numerical simulation.